Enhancing Ibuprofen Degradation through Optimization of ZrCo Synthesis Catalyst in Membrane Distillation - Luchmanandri, Rahmadini; Ali, Munawar; Murti, Restu Hikmah Ayu; Arale, Ade Lila (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
This study will optimize ZrCo as a catalyst applied to the surface of porous membranes to remove micropollutants, specifically ibuprofen. This method improves the reaction rate and accelerates the chain degradation of Ibuprofen, thereby preventing blockage caused by impurities in the membrane pores. The catalyst synthesis was performed using a hydrothermal method with ZrCl4 and CoCl2·6H2O as the primary materials. This method is employed to produce a high purity catalyst and yield a more stable catalyst. This research will measure the optimal catalyst through flux and removal efficiency during the membrane distillation process for 1 hour. Reaction conditions were adjusted using Air Gap Membrane Distillation at 80°C heating temperature, 4 L/min flow rate, and 1.5 mmol/L peroxymonosulfate as pre-oxidation. Experiments were conducted by comparing 9 types of catalysts, from which the best calcination temperature was selected for catalyst concentration optimization. Based on the flux and removal data tested statistically, the optimum catalyst type and calcination temperature were achieved at a 2:1 composition with a calcination temperature of 600°C, yielding flux and removal efficiency values of 7.0238 LMH and 98.53%. Meanwhile, the optimum catalyst concentration was obtained at 0.5 wt%, with flux and removal efficiency values of 8.05 LMH and 99.83%.